The builders of kabah: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story tells of the individuals involved in the construction of the Ka'bah, emphasizing their dedication and devotion. It highlights the historical and spiritual significance of this sacred site in Islam.